Planning Union Square as an Intercultural Center: Opportunities for a Diverse Community. - Tommee, Jong Wai. (2017)
Abstract: Urban communities throughout the nation are becoming increasingly diverse but not necessarily culturally connected. Intercultural Planning is a concept that sets the framework for deep understanding and acceptability of different groups to try to address this issue. Using Union Square, Somerville as a case study, a series of indicators determining the extent it is becoming intercultural is examined. How much have the city government and neighborhood associations embraced diversity, the sense of belonging of local ethnic businesses towards other groups, the representation of ethnic businesses in the chamber of commerce, and the effect of planning processes on intercultural planning including the proposed Green Line extension are among the indicators looked at. Union Square has been found to be very diverse and both the city government and various associations are working hard to promote the diversity. A few stakeholders even believe that Union Square is already intercultural to an extent. However certain obstacles remain including language barriers between different groups and the constant fear of unwanted changes that might destroy the community's opportunities before it even has the chance to be truly intercultural.; Thesis (M.A.)--Tufts University, 2012.; Submitted to the Dept. of Urban and Environmental Policy and Planning.; Advisor: Penn Loh.; Committee: James Jennings.; Keywords: Urban planning, and Public policy.